Caracterização agronômica, físico-química e sensorial de linhagens de pimenta (Capsicum chinense) - Toledo, Hugo Freitas de (Universidade Federal de São Carlos, 2024)
Consumed since before the arrival of Europeans on the American continent, peppers of the genus Capsicum hold great socioeconomic importance for Brazil, with 5 domesticated species. Among them, the most Brazilian of peppers, Capsicum chinense, characterized by its unique aroma and pungency, has been gaining increasing prominence with the deve-lopment of new cultivars, whether for resistance to pests and diseases, or to reach new market niches, such as the biquinho pepper, with very low pungency, enhanced aroma, and crispness. The current experiment aimed to characterize new Capsicum chinense pep-per lines and compare them with commercial cultivars (Maria Bonita, Biquinho, and Tui). The experiment was conducted in a greenhouse, followed by harvests and subsequent agronomic, physicochemical, and sensory evaluations of 10 Capsicum chinense lines from the UFSCar-BGUFSCar Genetic Improvement Program (F4 1902-2 pl1 alaranjado, F4 1902-2 4C creme, F4 1902-2 4C vermelho, F4 1907-2p pl2 creme, F4 1907-2p pl4 creme, F4 1907-3p pl2 alaranjado, F4 1907-3p pl3 alaranjado, F4 1907-4 pl2 alaranjado, F4 1907-6p pl1 vermelho, F4 1907-9p pl2 alaranjado), in addition to the 3 commercial cultivars used as controls. The peppers were evaluated for number of seeds per fruit (NSF), fruit length (CF), fruit diameter (DF), fruit length/fruit diameter ratio (CF/DF), pulp thickness (EP), number of locules (NL), total number of fruits per plant (NFT), average mass of total fruits (MMFT), total productivity (PTT), instrumental color (L*, a*, b*, hue, and C*), instrumental texture, titratable acidity (AT), soluble solids (SST), total soluble solids/titratable acidity ratio (SST/AT), and sensory analysis. Analysis of the evaluations revealed that F4 1907-4 pl2 alaranjado line stood out among the other lines in terms of agronomic and physicochemical aspects, with results similar to the Maria Bonita cultivar. In addition to this, the F4 1907-3p pl2 alaranjado line also showed promising results, and could be used for future improvements.
Agronomic, physical-chemical and sensorial characterization of pepper strains (Capsicum chinense)
Keywords: Melhoramento genético; Pimenta; Biquinho; Maria Bonita; Caracterização; Hortaliças; Análise sensorial; Avaliação agronômica; Avaliação físico-química; Cap-saicina; Pungência; Ardor; Capsicum chinense; Capsicum; Desenvolvimento; Variedades; Linhagens; Plant breeding; Genetic improvement; Pepper; Tui; Characterization; Pungency; Burning sensation; Lines; Development; Varieties; CIENCIAS AGRARIAS::AGRONOMIA